Distinguishing primate taxa with enamel incremental variables. Issue 164 (March 2022) - Kufeldt, Chrisandra; Wood, Bernard
Abstract: Enamel has long been of interest for its functional and phylogenetic significance among fossil hominins and other primates. Previous studies demonstrated that enamel incremental features distinguish among hominin fossil taxa, suggesting utility for highlighting taxonomy. However, not all features appear to be useful in mixed samples of fossils, living humans, and apes. Here we tested enamel incremental data from closely related primate taxa to determine which features, if any, distinguish among them. Enamel incremental variables were measured from the M2 of 40 living primate taxa, and we tested our variables using discriminant function analysis at the taxonomic ranks of parvorder, family, tribe, and genus. We then included enamel incremental data from Australopithecus afarensis, Australopithecus africanus, Paranthropus aethiopicus, Paranthropus boisei, and Paranthropus robustus to determine if these features distinguished fossil taxa from living humans and apes. Our initial results show that enamel incremental variables distinguish among primate taxa, but with low classification rates. Further testing with jackknifing methods shows overlap between groups at all taxonomic ranks, suggesting enamel incremental variables are unreliable for taxonomy. The addition of many common enamel incremental growth variables also resulted in multicollinearity in our multivariate analysis. As the dentition and isolated teeth remain a significant portion of the hominin fossil record, verifying enamel incremental features as a useful taxonomic tool is fundamentally important for hominin paleobiology.